ROTATING SPEED, RELIABILITY, ECONOMY, CHOOSING THE LAST STAGE TURBINE NPP - Канюк, Геннадий Иванович; Сухинин, Виктор Павлович; Погонина, Татьяна Евгеньевна; Бояршинов, Алексей Юрьевич; Фокина, Анна Ростиславовна; Михайский, Дмитрий Владимирович; Омельченко, Леонид Николаевич (Eastern-European Journal of Enterprise Technologies, 2012)
The analysis of designs of turbines at 1500 rev/min and 3000 rev/min is carried out. The characteristics of wet steam turbines are considered. Measures to ensure the reliability and efficiency of the turbine`s hard-grained part are analyzed.